Perancangan Sistem Analisa Kerusakan Mesin Sepeda Motor Matic Honda di Bengkel Berkah Jaya Gandaria Menggunakan Metode Forward Chaining - Sulthansyah Fahsani, Muhammad; Agustian, Bobi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Berkah Jaya Gandaria Garage is a Garage that handles various types of motor vehicle damage, especially automatic transmission vehicles. One way to deal with the damage is to do a thorough check on the motorcycle, but because the work takes too much time, an analysis system is made using the Forward Chaining method. The damage analysis process is carried out in many ways, such as looking at the engine and transmission as a whole. To support the analysis process, a damage system analysis is made that can search for symptoms or damage quickly and accurately. By using the Forward Chaining method, the performance of the system that has been running previously at Berkah Jaya Gandaria Garage is expected to improve with the analysis of this system.